(481) Needs and problems of education in Africa احتياجات ومشاكل التعليم في أفريقيا - Murice Dartigue (معهد التخطيط القومي, 2026)
This study examines the concept of educational needs in Africa as a multidimensional concept associated with the social, economic, and cultural objectives pursued by societies. The study argues that educational needs do not possess a fixed or universally defined meaning but vary according to societal values, priorities, and policy orientations. Educational needs may refer to quantifiable elements such as schools, teachers, and educational facilities, or to qualitative aspects such as curriculum adaptation and responsiveness to African cultural and environmental contexts. The study emphasizes that educational planning largely depends on accurately assessing educational requirements through the identification of objectives and their translation into quantitative and qualitative needs. Educational assessment should not be restricted solely to economic demands but should also incorporate individual aspirations and cultural development needs. The study highlights the interrelationship between individual and societal goals, emphasizing that education simultaneously contributes to personal development and to the preparation of qualified manpower required for economic and social progress. Two major approaches to educational needs assessment are discussed. The first is the manpower requirements approach, which focuses on predicting occupational structures and estimating future workforce needs. The second is the cultural approach, which emphasizes the broader role of education in promoting cultural development and human fulfillment. The study argues that sound educational policy requires the integration of both approaches. The study further identifies major educational needs across African countries, including expansion of educational opportunities, curriculum reform, teacher development, school construction, educational resources, vocational and technical education, girls’ education, adult education, and research related to African culture and agricultural development. The study concludes that effective educational development requires sound administration, sufficient financial support, and continuous institutional coordination.